Efficacy of fibrin sealant for bedside pleurodesis in patients with prolonged air leak after lung cancer surgery: a comparative study - Pan, Kaifang; Gu, Xin; Chen, Zhe; Yu, Jiahao; Xie, Kai; Liu, Jiangjiang; Qi, Jingkang; Wang, Bin; Xia, Haifeng (Frontiers in Surgery, 2026)
BackgroundProlonged air leak (PAL) represents a significant clinical problem after lung resection surgery, frequently causing extended hospital stays. Although several treatments exist, their effectiveness often remains limited. Fibrin sealant has attracted attention as a potential alternative due to its biocompatible properties, but strong evidence from controlled studies supporting its use for bedside pleurodesis remains insufficient. This study was conducted to compare the effectiveness and safety of fibrin sealant vs. 50% glucose solution in managing PAL following pulmonary resection for non-small cell lung cancer (NSCLC).MethodsWe performed a retrospective analysis of NSCLC patients who developed PAL (lasting ≥5 days) after surgery between January 2021 and May 2025. Patients received either fibrin sealant or 50% glucose solution for bedside pleurodesis. To address potential selection bias, we employed propensity score matching (1:1 ratio) based on key clinical characteristics. Primary outcomes included success rate after initial intervention and time to chest tube removal. Secondary outcomes focused on complication rates.ResultsAfter matching, 74 pairs were available for analysis. The fibrin sealant group showed significantly better outcomes, with a higher success rate after the first intervention (56.8% vs. 24.3%; OR = 4.08, 95% CI: 2.02–8.24, p < 0.001) and shorter time from intervention to median chest tube duration (6.0 days vs. 9.5 days, p < 0.001). All patients in the fibrin sealant group achieved resolution within three interventions, while some in the glucose group required up to seven procedures. Complication rates were similar between groups (16 cases each, p > 0.05), with no infection-related complications observed in the fibrin sealant group.ConclusionFor patients with PAL after NSCLC resection, bedside pleurodesis using fibrin sealant appears more effective than 50% glucose solution. It offers better initial success rates, significantly reduces air leak duration, and demonstrates a comparable safety profile. These findings support considering fibrin sealant as a primary non-surgical treatment option for this challenging complication.